2016
DOI: 10.1016/j.polymdegradstab.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Melt stabilization of polyethylene with dihydromyricetin, a natural antioxidant

Abstract: Experiments have been carried out to compare the stabilization effect of two flavonoid type natural antioxidants, dihydromyricetin (DHM) and quercetin (Q) in polyethylene (PE). Additive concentrations changed between 0 and 500 ppm in several steps and 1000 ppm Sandostab PEPQ phosphorus containing secondary stabilizer was also added to each compound. Both antioxidants are very efficient stabilizers for PE, sufficient melt stability was achieved already at 50 ppm DHM content. At small concentrations dihydromyric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 43 publications
2
39
0
2
Order By: Relevance
“…The goal was to study the dispersion and controlled release effect and not the development of an industrial package. All our studies on natural antioxidants showed that flavonoids usually are much more efficient than traditional phenolic antioxidants currently used in industrial practice [17][18][19][20].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The goal was to study the dispersion and controlled release effect and not the development of an industrial package. All our studies on natural antioxidants showed that flavonoids usually are much more efficient than traditional phenolic antioxidants currently used in industrial practice [17][18][19][20].…”
Section: Introductionmentioning
confidence: 92%
“…The number of potential natural compounds which might be used as antioxidant in polyolefins is very large and only several of them have been studied in stabilization experiments up to now. The antioxidant effect of curcumin [17], quercetin [18] and dihydromyricetin [19] was studied in a Phillips type polyethylene in the presence of a phosphorous secondary stabilizer and the stabilization efficiency of all three exceeded considerably that of the synthetic phenolic antioxidant routinely used in large quantity in industrial practice. The efficiency of another natural antioxidant, silymarin, a flavonolignan compound with the same basic structure as quercetin proved to be much less efficient [20].…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of the compounds in polyethylene was estimated from changes in the color of the polymer as a function of antioxidant content. In a series of recent studies, Phillips type polyethylene samples containing various amounts of the antioxidants listed in Table 3 and PEPQ secondary stabilizer were produced by multiple extrusions [114][115][116][117]. Their efficiency as processing stabilizer was determined and it was shown to depend on their chemical structure, dispersion and interaction with the secondary antioxidant.…”
Section: Application In Polymersmentioning
confidence: 99%
“…From an industrial standpoint, however, one may need to combine properties of different additives to gain a “multifunctional” additive that may bring about several benefits to PP polymer. The use of a multifunctional additive rather than mixture of additives with different functionalities leads to facilitation of processing and facile dispersion of additives into the molten polymer . Therefore, there has been a great deal of research to find appropriate ways for tailoring properties of different additives into a unique versatile additive as the next generation of high‐performance multifunctional derivatives—what brings about new challenges in spite of being interesting .…”
Section: Introductionmentioning
confidence: 99%